Synthesis and herbicidal activity of novel pyrazole aromatic ketone analogs as HPPD inhibitor. Issue 3 (10th September 2019) - Fu, Qing; Cai, Peng‐Peng; Cheng, Long; Zhong, Liang‐Kun; Tan, Cheng‐Xia; Shen, Zhong‐Hua; Han, Liang; Xu, Tian‐Ming; Liu, Xing‐Hai
Abstract: BACKGROUND: 4‐Hydroxyphenylpyruvate dioxygenase (HPPD, EC 1.13.11.27) has been a good target for herbicide discovery. In order to discover novel HPPD herbicides, a series of pyrazole aromatic ketone analogs were designed and synthesized. RESULTS: The 25 pyrazole aromatic ketone analogs synthesized were tested for herbicidal activity and compounds A1, A3, A4, A17, A20 and A25 displayed excellent herbicidal activity against Chenopodium serotinum, Stellaria media and Brassica juncea at 37.5 g ha −1 . In addition, compounds A1, A5, A9, A10, A16, A17, A20 and A25 exhibited good crop selectivity for wheat, maize and rice at 150 g ha −1 . Inhibition activities against At HPPD proved the compounds were HPPD inhibitors. The structure–activity relationship of these pyrazole aromatic ketone analogs was studied using molecular docking. CONCLUSION: These pyrazole aromatic ketone derivatives could be used as lead structures for development of HPPD herbicides against dicotyledonous weeds with further structure modification. © 2019 Society of Chemical Industry Abstract : Due to herbicide resistance, we need to discover novel herbicides. In this paper, we introduce a flexible chain into the pyrazoxyfen, new compounds were synthesized and they exhibited good herbicidal activity. We found that these compounds are safe for monocotyledon crops and can be used as herbicides in the corn, wheat or rice field. The mode of action (MOA) is 4‐hydroxyphenylpyruvate dioxygenase and can be optimized further to discover new herbicides. Much research is focused on the mimics of triketones. Nowadays, heterocycles are an important route to discover new agrochemicals, so this paper will enable argochemists to discover new HPPD inhibitors.